Diversity and Abundance of Butterflies (Insecta: Lepidoptera) in Forest and Residential Areas on the Slopes of Mount Karang, Banten - Jasmi, Riski Andrian; Musthopa, Muhamad Huda; Hanafiah, Raihan Imam; Febryansyah, Azmy; Badaruddin, Alfito; Iqramifta, Abil; Sari, Herlina Putri Endah (Biotropika: Journal of Tropical Biology, 2026)
Butterflies play an important ecological role as pollinators and as biological indicators of habitat quality. However, information on butterfly diversity and abundance in the Mount Karang region of Banten has never been reported, creating a gap in the baseline biodiversity data for this area. This study aims to analyse the diversity, abundance, and distribution patterns of butterflies (Insecta: Lepidoptera) in two contrasting habitat types: the Canggoang Forest and the residential area of Juhut Village on the slopes of Mount Karang. Field sampling was conducted over eight days between September and October 2025 using direct capture methods (insect nets) in the morning and afternoon. Butterfly communities were analysed using biodiversity indices, and structural comparisons between the two habitats were assessed using the Jaccard and Bray–Curtis indices. A total of 23 species were recorded in the forest and 28 species in the residential area. Nymphalidae and Pieridae dominated both locations, while Papilionidae, Lycaenidae, and Hesperiidae were found in smaller numbers. Diversity values indicated a moderate level of species richness, with low dominance and high evenness. Species richness was categorised as high in both habitats. Variation in vegetation structure, availability of host plants, and microclimatic factors—particularly temperature, humidity, and wind speed—were identified as the main factors shaping butterfly communities. These findings provide the first comprehensive baseline data on butterfly biodiversity in the Mount Karang area and highlight the importance of maintaining heterogeneous habitat conditions to support both generalist and specialist species. The results also underscore the relevance of integrating butterfly diversity assessments into local conservation strategies and landscape management.